2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649364
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between a matrix-based and a region-based P300 speller paradigms for brain-computer interface

Abstract: A brain-computer interface (BCI) is a system that conveys messages and commands directly from the human brain to a computer. The BCI system described in this work is based on P300 wave. The P300 is a positive peak of an event-related potential (ERP) that happens 300 ms after a stimulus. One of the most well-known and widely-used P300 applications is P300 speller designed by Farwell-Donchin in 1988. The Farwell-Donchin paradigm has been a benchmark in P300 BCI. In this paradigm, a 6x6 matrix of letters and numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Recent work has shown that P300 BCIs can be used for a wide range of different functions and can work with disabled users in home settings (Kübler et al, 2009; Sellers et al, 2010; Kleih et al, 2012), although some concerns about gaze shifting have emerged (Allison et al, 2008; Brunner et al, 2010; Treder and Blankertz, 2010). In addition, new paradigms for eliciting the P300 have been introduced (Fazel-Rezai and Abhari, 2009; Townsend et al, 2010), and new ways to flash or otherwise change stimuli could enhance ERPs and improve classification (Kaufmann et al, 2011; Jin et al, 2012). Overall, it is likely that P300 BCIs will remain prominent in the foreseeable future, but will probably grow further and further away from the canonical 6 × 6 matrix with single row and column flashes described in the first two P300 BCI articles.…”
Section: Current Status Of P300 Bcismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that P300 BCIs can be used for a wide range of different functions and can work with disabled users in home settings (Kübler et al, 2009; Sellers et al, 2010; Kleih et al, 2012), although some concerns about gaze shifting have emerged (Allison et al, 2008; Brunner et al, 2010; Treder and Blankertz, 2010). In addition, new paradigms for eliciting the P300 have been introduced (Fazel-Rezai and Abhari, 2009; Townsend et al, 2010), and new ways to flash or otherwise change stimuli could enhance ERPs and improve classification (Kaufmann et al, 2011; Jin et al, 2012). Overall, it is likely that P300 BCIs will remain prominent in the foreseeable future, but will probably grow further and further away from the canonical 6 × 6 matrix with single row and column flashes described in the first two P300 BCI articles.…”
Section: Current Status Of P300 Bcismentioning
confidence: 99%
“…The idea of region-based (RB) paradigm (Fazel-Rezai and Abhari, 2009) is to have flashes of several regions instead of rows and columns. The character recognition is performed in two levels (Fazel-Rezai and Ahmad, 2011).…”
Section: Visual P300 Paradigmsmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 5 Although the RC paradigms with its variants is still the most famous paradigm, several other types of paradigms have also been presented in recent times including Single Character (SC) paradigm (Guan, Thulasidas, & Wu, 2004), Region-Based (RB) paradigm (Fazel-Rezai & Abhari, 2008;Fazel-Rezai & Abhari, 2009), Check Board (CB) paradigm and Rapid Serial Visual Presentation (RSVP) based paradigm (Acqualagna & Blankertz, 2013;Acqualagna, Treder, Schreuder, & Blankertz, 2010). Although most of the P300 speller paradigms are developed for English language, P300 BCI with other alphabets, such as alphabets in Chinese (Jin et al, 2010;Minett et al, 2012) , Japanese (Yamamoto, Yoshikawa, & Furuhashi, 2015) and Arabic languages (Kabbara, Hassan, Khalil, Eid, & El-Falou, 2015) have also been published.…”
Section: Downloaded By [University Of California Santa Barbara] At 19mentioning
confidence: 99%
“…The list of characters used in seven regions in the first level of this modified edition is presented in Table 2. In a comparative study, it was found that the overall spelling accuracies averaged for the same set of subjects, trials, and characters for RC, SC, and two variations of RB paradigms were 85, 72.2, 86.1, and 90.6%, respectively [14,69]. It is interesting to note that other than P300 BCI, application of RB paradigm has been extended to other BCI modalities too [54,[70][71][72].…”
Section: Region-based (Rb) Paradigmmentioning
confidence: 99%